2021
DOI: 10.3390/ijms222212552
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiological Properties and Clinical Applications of Interleukin-38 for Immune-Mediated Disorders: A Systematic Review Study

Abstract: Exponential growth in the usage of “cytokines” (as seroimmunobiomarkers) has facilitated more accurate prognosis, early diagnosis, novel, and efficient immunotherapeutics. Numerous studies have reported immunopathophysiological and immunopathological processes of interleukin-38 (IL-38). Therefore, in this systematic review article, the authors aimed to present an updated comprehensive overview on the immunobiological mechanisms, diagnostic, and immune gene-based therapeutic potentials of IL-38. According to ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 195 publications
0
5
0
Order By: Relevance
“…IL-38 is thought to be an ancestral gene intended to counteract the pro-inflammatory effects of IL-1 (136). In humans, IL-38 is found in several organs such as the tonsils, skin, fetal liver, heart, and placenta, but in future studies it will certainly be found in many other organs (137). The anti-inflammatory effect of IL-38 is homologous with two anti-receptors, IL-36Ra (about 40%) and IL-1Ra (about 40%), sharing the anti-inflammatory effect (138).…”
Section: Il-38 Dumping Il-1 Induced Inflammationmentioning
confidence: 96%
“…IL-38 is thought to be an ancestral gene intended to counteract the pro-inflammatory effects of IL-1 (136). In humans, IL-38 is found in several organs such as the tonsils, skin, fetal liver, heart, and placenta, but in future studies it will certainly be found in many other organs (137). The anti-inflammatory effect of IL-38 is homologous with two anti-receptors, IL-36Ra (about 40%) and IL-1Ra (about 40%), sharing the anti-inflammatory effect (138).…”
Section: Il-38 Dumping Il-1 Induced Inflammationmentioning
confidence: 96%
“…The study concluded that IL‐38 may exert a protective role against immune system hyperactivity, and may alleviate induced lung inflammation 11 . Besides, it has been indicated that dysregulated serum levels of IL‐38 are linked to immunopathogenesis of several inflammatory and immune‐mediated disorders, as well as lung‐related diseases 12 …”
Section: Introductionmentioning
confidence: 99%
“… 11 Besides, it has been indicated that dysregulated serum levels of IL‐38 are linked to immunopathogenesis of several inflammatory and immune‐mediated disorders, as well as lung‐related diseases. 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interleukin‐38 (IL‐38) is a member of the IL‐1 family, which binds to IL‐36 receptor (IL1RL2) as an antagonist to exert an anti‐inflammation effect (Esmaeilzadeh et al, 2021 ; Lai et al, 2022 ; van de Veerdonk et al, 2012 ). Also, IL1RL2 was reported as a candidate gene‐related soluble ST2 those elevated levels reflected the degree of vascular injury (Jiang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%